2019
DOI: 10.1002/jcb.29310
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of bicyclol against pulmonary fibrosis via regulation of microRNA‐455‐3p in rats

Abstract: Idiopathic pulmonary fibrosis (IPF), a chronic, progressive and irreversible disease, needs long‐term treatment. Bicyclol was found to play a great role in pulmonary fibrosis, and the present study is to explore how bicyclol affects IPF with the involvement of microRNA‐455‐3p (miR‐455‐3p) and Bax. Bleomycin (BLM) was used to induce the IPF model in Sprague‐Dawley rats to detect the expression of miR‐455‐3p, Bax, and B‐cell lymphoma factor 2 (Bcl‐2). Moreover, to further investigate the mechanisms of bicyclol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
(86 reference statements)
1
12
0
Order By: Relevance
“…miR-455-3p is lowly expressed in various tumors, including prostate (31), colorectal (32), pancreatic (33) and breast cancer (34). miR-455-3p serves as an important regulator in organ fibrosis, including pulmonary fibrosis (10,35,36). The present study found that the miR-455-3p inhibitor partially reversed the regulatory effects of shRNA-NEAT1-1 on EMT and collagen generation.…”
Section: Discussionsupporting
confidence: 50%
“…miR-455-3p is lowly expressed in various tumors, including prostate (31), colorectal (32), pancreatic (33) and breast cancer (34). miR-455-3p serves as an important regulator in organ fibrosis, including pulmonary fibrosis (10,35,36). The present study found that the miR-455-3p inhibitor partially reversed the regulatory effects of shRNA-NEAT1-1 on EMT and collagen generation.…”
Section: Discussionsupporting
confidence: 50%
“…Previous study showed that miR-455-3p could act as a fibrogenesis suppressor. It may exert its role by potentially binding to Bax gene to suppress apoptosis of alveolar epithelial cells [35]. Notch2 is one of the most important members of Notch receptor family, composed of 34 exons and encoded by 2471 amino acids [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-455-3p has been demonstrated participating in fibrosis. For instance, upregulation of miR-455-3p could suppress idiopathic pulmonary fibrosis through repression of Bax expression [27]. miR-455-3p overexpression suppressed renal fibrosis through repressing Rho-associated protein kinase 2 (ROCK2) expression [28].…”
Section: Discussionmentioning
confidence: 99%